Switching phenomena between laminar and turbulent flows of superfluid He-4 generated by a vibrating wire - Hashimoto, N; Handa, A; Nakagawa, M; Obara, K; Yano, H; Ishikawa, O; Hata, T (2007)
We have investigated the turbulence transition of the superfluid 4He flow generated by a vibrating wire. For a 1.2-kHz vibrating wire, we observed intermittent switchings between laminar and turbulent flows. The switching rate decreases with increasing temperature above 100 mK, until no occurrence of the switchings at 350 mK. For a 2.4-kHz vibrating wire, we find that the switching rate is much lower than that of the 1.2-kHz vibrating wire even at low temperatures. This result indicates that a mechanism causing the switchings is influenced by the temperature and the oscillation frequency of the superfluid flow. © Springer Science+Business Media, LLC 2007.